The Effects of Kingbo Biopesticide on Tetranychus urticae Koch Female Adults - Međo, Irena S; Marčić, Dejan S (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Toxic and sublethal effects of the biopesticide Kingbo (oxymatrine 0.2% + psoralen 0.4%) on female adults of two-spotted spider mite (Tetranychus urticae Koch) were investigated in two laboratory bioassays. The assays were set up in four replicates on bean leaf discs (30 mm in diameter) placed on moistened cotton wads in Petri dishes. Pre-ovipositional females were then released on them and treated directly with the biopesticide at a concentration series using a Potter device (2 ml liquid, 100 kPa air pressure, 2.7 ± 0.2 mg/cm2 aqueous deposit). Each replicate included 4-7 Petri dishes containing a total of 20-35 females. In the first assay, females were exposed to continuous acaricidal activity on treated discs over a period of 96 h; in the second assay, they were exposed for 24 h and then transferred to untreated discs and kept there for the next 72 h. Kingbo toxicity to females, expressed as LC50, was significantly higher in the first bioassay (14.83 μl/l) than in the second one (26.39 μl/l). Total gross fecundity of females in the first assay was reduced by 37-95% and net fecundity by 48-97%, depending on concentration; in the second assay, the respective fecundity reductions were 15-87% and 23-91%. We found that a 24 h exposure to the biopesticide Kingbo was sufficient for sustaining significant toxic and sublethal effects. Further research should provide additional data on the recovery potential of T. urticae populations.